The Functions of Music in the Film and its Effect on the Audience - Ali Khaled Ali; Kamal Ahmed Sherif; Wael Mohammed Anany (Journal of Architecture, Art & Humanistic Science, 2023)
The film and the music participate in dividing the element of time into well-defined rhythm patterns. There are certain natural rhythms that are inherent in the physical movements of many of the visual elements on the screen, from trees driven by the wind, footsteps, a car engine, etc., all of this creates natural rhythms. Creates an instinctive need to hear rhythmic sounds corresponding to the visual.The rhythmic pattern is also provided by the pace of the plot, by controlling how fast or slowly it develops. As well as by creating a rhythm by controlling the pace of dialogue and the natural rhythms of dialogue between characters. Tempo tempo is determined by repeating combination bits and controlling the duration of each shot between one cut and the next, giving each scene a unique rhythmic character. Although the synthesis "montage" divides the film into a number of separate parts, but it achieves sequence and flowing form, because the music possesses these same qualities of rhythm and continuity, and can easily adapt to the basic rhythms of the film.Music has a very great effect on the spectator's response, as it increases the reactions of almost any movie. Where music works to achieve a set of basic functions, namely:Create structural rhythms.Support and strengthen the emotional content of the image.Expressing emotions that cannot be conveyed through the visual image.Provoke imagination, emotional responses, stimulation of thoughts and the subconscious.Complementing and enhancing the dramatic and narrative structure by eliciting the emotional and emotional responses that parallels each single scene and the film as a whole.The research discusses the types and functions of music within the film, and the relationship between visual and audio variables, in order to find out how to balance between visual and technical dazzling, and between the desired contents of the film.